2019
DOI: 10.2196/11780
|View full text |Cite
|
Sign up to set email alerts
|

Flucast: A Real-Time Tool to Predict Severity of an Influenza Season

Abstract: Background Influenza causes serious illness requiring annual health system surge capacity, yet annual seasonal variation makes it difficult to forecast and plan for the severity of an upcoming season. Research shows that hospital and health system stakeholders indicate a preference for forecasting tools that are easy to use and understand to assist with surge capacity planning for influenza. Objective This study aimed to develop a simple risk prediction tool, Flucast, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Kandula et al ( 93 ) developed a compartmental model for predicting influenza hospitalization rates using Google search trends. Moa et al ( 94 ) proposed a linear model to forecast the overall severity of an influenza season in Australia based on only five parameters.…”
Section: Decision Supportmentioning
confidence: 99%
“…Kandula et al ( 93 ) developed a compartmental model for predicting influenza hospitalization rates using Google search trends. Moa et al ( 94 ) proposed a linear model to forecast the overall severity of an influenza season in Australia based on only five parameters.…”
Section: Decision Supportmentioning
confidence: 99%
“…The internal application contains full data access, dashboards with relevant visualizations (for mapping, statistical analytics, searching, or decision support), a user administration panel, and searchable access to the database. EPIWATCH is supplemented by the development of tools such as a seasonal influenza forecasting tool (FLUCAST), 7 an epidemic risk analysis tool (EPIRISK), 8 and a tool for determining the origins of epidemics, 9 all of which have been tested through rigorous research.…”
Section: Main Textmentioning
confidence: 99%
“…1 The predicted severity of seasonal influenza is not well understood but often depends on the predominate subtype in the circulation, vaccination coverage in the population, and the individual immune response of infected persons. 2 Studies have frequently observed higher rates of hospitalization and reduced vaccine effectiveness among A/H3N2 predominate seasons when compared to seasonal A/H1N1pdm09 (and the pre-pandemic seasonal A/H1N1) and influenza B viruses. [3][4][5] Increased disease burden and mortality in elderly people and children have also been associated with A/H3N2 infection compared with other seasonal strains, 6,7 while influenza B typically causes disproportionate morbidity and mortality in children.…”
Section: Introductionmentioning
confidence: 99%
“…Influenza A/H3N2 is one of four subtypes that circulate seasonally in humans every year causing annual epidemics in both temperate and tropical regions; the others being influenza A H1N1pdm09 (A/H1N1pdm09) and influenza B Yamagata (B/Yam) and Victoria (B/Vic) 1 . The predicted severity of seasonal influenza is not well understood but often depends on the predominate subtype in the circulation, vaccination coverage in the population, and the individual immune response of infected persons 2 . Studies have frequently observed higher rates of hospitalization and reduced vaccine effectiveness among A/H3N2 predominate seasons when compared to seasonal A/H1N1pdm09 (and the pre‐pandemic seasonal A/H1N1) and influenza B viruses 3‐5 .…”
Section: Introductionmentioning
confidence: 99%